Meta-Analisis Efektivitas Model Pembelajaran PBI (Problem Based Instruction) Pada Matematika Tingkat Sekolah Dasar - Rodhiyah Eni Mukhlisa Putri (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the effectiveness of the Problem Based Instruction (PBI) learning model in Mathematics at the Elementary School level. The average percentage of learning outcomes before using the Problem Based Instruction learning model is 49.99% and the average percentage of learning outcomes before using the Problem Based Instruction learning model is 71.49%. So it has increased by 21.50%. The average value of experiment 1 is lower than the average value of experiment 2. The significance value is 0.003 (0.003 < 0.005). So it can be said that the PBI learning model has little effect on elementary mathematics outcomes.